x+(70000*.09)=70000

Simple and best practice solution for x+(70000*.09)=70000 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+(70000*.09)=70000 equation:


Simplifying
x + (70000 * 0.09) = 70000

Multiply 70000 * 0.09
x + (6300) = 70000
x + 6300 = 70000

Reorder the terms:
6300 + x = 70000

Solving
6300 + x = 70000

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6300' to each side of the equation.
6300 + -6300 + x = 70000 + -6300

Combine like terms: 6300 + -6300 = 0
0 + x = 70000 + -6300
x = 70000 + -6300

Combine like terms: 70000 + -6300 = 63700
x = 63700

Simplifying
x = 63700

See similar equations:

| (v-1.4)(v+1.4)= | | 25v^2-49= | | 9(x+11)+5(13x)=0 | | (-1-2m)(5-3m)= | | x+3y=776 | | 7y+2=51 | | 12x^2-16x-3=0 | | 5a^2+24a-5= | | x+y=250 | | 2x-9=-8 | | 2*-9=-8 | | 3p^2=-4p-1 | | 3x^2=4x+11 | | 2x+5y=1252x-y-10 | | 2x+5y=125 | | -4y=12x+13 | | 30*8.50*52= | | -4x-6+x=-2x-x-10 | | y^2=-27 | | 8x-51=10x-57 | | 6x+1-3=2x+4(1+x) | | -8m^2-8n^2=-40 | | 6(25-x)+10=-15x+242 | | -z+7z=-7z-5+4z | | b^2+5bd-14d^2= | | 0=y^3-4y | | 5(4x-4)-1=20x-21 | | b^2-4b-14=2 | | 9x-4=6x+17 | | 8-5x-5-5x=5 | | 45.8+18.3(15.1-16.1)= | | 3x+14=9x-4 |

Equations solver categories